HASIL TES URINE SEBAGAI BUKTI PERMULAAN YANG CUKUP UNTUK MENETAPKAN TERSANGKA PADA PERKARA TINDAK PIDANA NARKOTIKA - Aditya Prima Mabrury (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2021)
Abstract Urine test is one of the methods used to prove the existence of Narcotics substances in a person's body. In the context of carrying out the task of eradicating illicit abuse and illicit trafficking of Narcotics and Narcotics Precursors, the investigator has the authority to conduct urine tests on a person suspected of being an abuser, as stipulated in Article 75 letter l of Law Number 35 Year 2009 concerning Narcotics. The urine sample that has been taken will then be tested based on the development of science and technology in the narcotics testing laboratory which is then poured in the minutes of the test results. The minutes of the test results are valid evidence as determined by Article 184 of the Criminal Procedure Code. Someone who has a positive urine test result can be arrested and named as a suspect of narcotics abuse based on sufficient preliminary evidence. Suspects of abuse of Narcotics can be convicted in accordance with Article 127 paragraph (1) of the Narcotics Act. Thus the legal issues in this study is the Urine Test Results Are Used as the Basis for Assigning a Person to Be a Narcotics Abuse and Classification of Urine Test Results as Evidence As a Provision for Article 184 of the Criminal Procedure Code. Keywords: Urine Test, Preliminary Evidence, Determination of Suspect, Valid Evidence. Abstrak Tes urine merupakan salah satu metode yang digunakan untuk membuktikan adanya kandungan zat Narkotika dalam tubuh seseorang. Dalam rangka melaksanakan tugas pemberantasan penyalahgunaan dan peredaran gelap Narkotika dan Prekursor Narkotika penyidik berwenang melakukan tes urine terhadap seseorang yang diduga sebagai penyalah guna, sebagaimana diatur pada Pasal 75 huruf l Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika. Sampel urine yang telah diambil selanjutnya akan diuji berdasarkan perkembangan ilmu pengetahuan dan teknologi di laboratorium uji narkotika yang kemudian dituangkan dalam berita acara hasil pengujian. Berita acara hasil pengujian merupakan alat bukti yang sah sebagaimana ditentukan Pasal 184 KUHAP. Terhadap seseorang yang hasil tes urinenya positif dapat ditangkap dan ditetapkan sebagai tersangka penyalahgunaan Narkotika berdasarkan bukti permulaan yang cukup. Tersangka penyalahgunaan Narkotika dapat dipidana sebagaimana ketentuan Pasal 127 ayat (1) Undang-Undang Narkotika. Dengan demikian rumusan masalah dalam penelitian ini adalah Hasil Tes Urine Dijadikan Dasar Untuk Menetapkan Seseorang Sebagai Tersangka Penyalahguna Narkotika dan Klasifikasi Hasil Tes Urine Sebagai Alat Bukti Sebagaimana Ketentuan Pasal 184 KUHAP. Kata Kunci: Tes Urine, Bukti Permulaan, Penetapan Tersangka, Alat Bukti Yang Sah.